Beef Cow-Calf Enterprise - Dhuyvetter, Kevin C.; Langemeier, Michael; Johnson, Sandy (My University, 2009)
This publication provides a budget based on projected input and output prices. This budget is based on a typical spring calving cow herd with natural breeding.
MF266_2009_12
Keywords: MF266; Livestock; Economics; MF